Effects of Managerial Ownership Structure, Firm Size, and Practices Corporate Governance on Profit Management (Literature Reviews) - Vio Letty Risanli (Dinasti Publisher, 2023)
LiteraturexReview Article Effects of Managerial OwnershipxStructure, Firm Size, and PracticesxCorporate Governance on Earnings Management is a scientificx article that aimsx to build a researchx hypothesisx on the influence betweenx variables to be usedx in furtherx research, withinx the scopex of the sciencex of xFinancial xManagement. The method xof xwriting this Literature Review xarticle is by methodxresearch library, xsourced from online media such asxGoogle Scholar, Mendeleyxand xmediaon xlineother xacademics. The xresults of this literature review article arex: 1) Managerial Ownership Structure influences earningsx management; 2) company size influences xearnings xmanagement; and 3) corporatex governancex practicesx affectx earningsx management.